ECONOMIC CONTRIBUTIONS OF THE CARABAO TO FARM HOUSEHOLDS AND RESOURCE PRODUCTIVITY ANALYSES - Pascual, Nerelito P.; Pañares, Edgardo A. (Annals of Tropical Research, 1984)
Majority of the carabaos raised by farmers in Iloilo, Bohol and Leyte are intended primarily for draft purpose. Among the six types of farming systems, the carabao used for rice-based farming had the highest value of draft power and the lowest was in sugarcane-based farming. The value of work done per year was highest in medium-sized farms, followed by those in large farms and small-sized farms based on both on-farm and off-farm operations in the three provinces. The animal work days per year ranged from an average of 23 days in small-sized farms to 37 days in medium-sized ones with an overall average of 30 days. Only three farmer respondents with one carabao each were milking their carabaos primarily for home use. Multiple regression analysis showed no significant relationship between number of work days and items of expenditure like depreciation, biologics and fees. Labor and cost of supplies and materials were found to be positively related to the number of work days. Total value of the economic contribution to the farm household showed no significant relationships with depreciation, supplies and materials, biologics and fees. Labor cost had a significant negative effect while farms size showed a positive effect on the total value of the economic contribution of the carabao to the farm household.